Evaluation and Strategy for the Improvement of the MBKM Program at the Department of Architecture, Universitas Pembangunan Jaya - PURISARI, Rahma; PURWANTO, Dr. Edi; ADENIA, Irviananda; AGUSTA, Salina Widiya Putri; PRASETYORINI, Sekar Arum (CENTRAL ASIA AND THE CAUCASUS, 2021)
Merdeka Belajar Kampus Merdeka (MBKM) is a concept that requires universities to design and implement innovative learning processes. This program is a solution to the demands of independent and flexible forms of learning in higher education, so as to create a learning culture that is innovative, unfettered, and in accordance with the needs of students. Likewise, Universitas Pembangunan Jaya, which is one of the Independent Campuses, has continued to encourage the implementation of this program since its inception. In line with the university's steps, the Department of Architecture quickly plans an MBKM program that aims to encourage students to master various sciences that are useful for entering the world of work. After one year of the MBKM program with four forms of running activities in the Department of Architecture, the researchers wanted to evaluate the implementation of that one, because a program definitely must have success and obstacles faced. Thus, this study aims to evaluate the running of the MBKM program in the Department of Architecture and provide strategic suggestions for improving program implementation. The research method used was a combination of quantitative and qualitative with the respondents involved were students and lecturers of the Department of Architecture. By using a SWOT analysis and cross-matrix strategy, this research resulted in an evaluation of activities and proposed strategies in improving the MBKM program for the sustainability of the program in the future.